IMPLEMENTASI PERATURAN DAERAH KOTA PEKANBARU NOMOR : 7 TAHUN 2016 TENTANG PENYELENGGARAAN ADMINISTRASI KEPENDUDUKAN - Febri Yuliani, Safriah Dalimunthe, Zaili Rusli, (Jurnal Ilmu Administrasi Negara, 2020)
Implementation Of Peraturan Daerah Kota Pekanbaru Nomor 7 Tahun 2016 Ten-tang Penyelenggaraan Administrasi Kependudukan Pada In Dinas Kependudukan Dan Pen-catatan Sipil Pekanbaru City. This research was motivated by the Peraturan Daerah Kota Pek-anbaru nomor 7 tahun 2016 changes of Perda nomor 5 tahun 2008 about Penyelenggaraan Admin-istrasi Kependudukan dan Pelayanan Publik. During the past 3 (three) years, problems in imple-mentation were found, one of which was that the Perda was not well socialized to the public. The purpose of this study was to determine the implementation of Peraturan Daerah Kota Pekanbaru nomor 7 tahun 2016, and analyze the factors that inhibit the implementation of Peraturan Daerah Kota Pekanbaru nomor 7 tahun 2016. This study used a descriptive qualitative research method approach. Primary data obtained directly through interviews from informants, namely the Staff, the Heads of Divisions and the Heads of Sub Divisions in the Disdukcapil Pekanbaru City as the im-plementor. The results of this study show that the implementation of Peraturan Daerah Kota Pek-anbaru nomor 7 tahun 2016is not good, this is indicated by the non-socialization of this regulation to the public and only through local area officials such as the Camat and Lurah who only use via internet or cellular telephone plus there are still human resources weak both in computer use and education skills.